Two novel mutations in VPS33B gene cause a milder ARC syndrome with prolonged survival in a 12-year-old patient: Case report - Zhu, Yingjie; Chen, Dongmei (Frontiers in Pediatrics, 2022)
Arthrogryposis-renal dysfunction-cholestasis (ARC) syndrome is a rare autosomal recessive disease caused by VPS33B and VIPAR gene mutations. The main clinical manifestations are congenital joint contracture, renal dysfunction mainly characterized by distal renal tubular dysfunction, and low glutamyltransferase cholestasis. Most patients with ARC die within 2 years of birth. We report a case of a 12-year-old girl with an ARC phenotype who experienced long-term survival with only mild clinical symptoms. We detected two new heterozygous mutation sites of VPS33B gene in this child: c.1081C>T (p.GLN361X, 257) and c.244T>C(p.Cys82Arg), through gene detection technique; the tertiary structure of protein was predicted by SWISS-model. We further reviewed the literature and summarized the clinical manifestations and gene loci of 19 ARC syndrome patients with long-term survival reported so far.